Environment-friendly cross-linking type shield mud system and preparation method thereof
Patent Information
- Application Number
- CN202410467701.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-18
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-04-18
AI Technical Summary
[0006]为了改善常规泥水盾构泥浆体系性能参数难以控制,支护效果不佳的缺陷,本申请提供一种绿色环保交联型盾构泥浆体系及制备方法
[0028]1、聚丙烯酰胺本身无腐蚀,无毒性,并且被认为不可降解为其单体AM,用量少并且聚丙烯酰胺本身就是一种土壤改良剂,可以增加土壤的团粒结构,分子中含有的酰胺基在土壤中缓慢水解,可增加土壤的含氮量,故对农田和环境污染大大减轻。
Smart Images

Figure CN118515451B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the technical field of tunnel shield slurry, and more specifically, it relates to a green and environmentally friendly cross-linked shield slurry system and its preparation method. Background Technology
[0002] With the continuous increase in total population and population density in some areas, the demand for underground space development is also constantly increasing. Among them, underground shield tunneling technology is widely used in tunnel plazas due to its advantages such as fast progress, accurate tunnel structure shape, minimal impact on ground structure, safety, minimal environmental impact, and high engineering quality.
[0003] The traditional slurry materials used in slurry tunnel boring machines (TBMs) mainly consist of natural clay, bentonite, water, and other compounds such as the thickener CMC. Bentonite is a mineral with limited global reserves, and much of what is sold as bentonite is actually polymer-modified bentonite treated with anionic low-molecular-weight Na-CMC or synthetic polymer additives. In terms of operating site area, traditional slurry requires bentonite hydration tanks and complex separation and treatment plants for reuse and disposal. This is because clay slurry absorbs a large amount of soil particles that are difficult to remove due to their yield strength. In several countries and regions, environmental concerns have been raised about this mixed waste material, and its use has been banned in some sensitive areas.
[0004] In addition, the performance parameters of traditional bentonite mud are difficult to control, and a large amount of waste mud is generated during construction. During the infiltration process, it is easy to cause water and soil pollution. Especially in areas with high water quality requirements, once fracturing or excessive mud seeps into the groundwater, it can easily pollute the water quality and affect the drinking water health of surrounding residents.
[0005] Therefore, there is an urgent need for a cross-linked shield tunneling mud system that can reduce the amount of traditional bentonite used while providing excellent support. Summary of the Invention
[0006] To address the shortcomings of conventional slurry shield tunneling systems, such as difficulty in controlling performance parameters and poor support effects, this application provides a green and environmentally friendly cross-linked shield tunneling slurry system and its preparation method.
[0007] Firstly, this application provides a green and environmentally friendly cross-linked shield tunneling mud system, employing the following technical solution:
[0008] A green and environmentally friendly cross-linked shield tunneling mud system comprises the following raw materials in parts by weight: 90-110 parts water, 0.03-0.15 parts thickening and slag-polymerizing agent, 1-3 parts bentonite, 0.01-0.18 parts soda ash, 0.02-0.06 parts cross-linking agent, 0.01-0.15 parts loss-reducing agent, and 0.01-0.10 parts emulsifier, wherein the thickening and slag-polymerizing agent is hydrolyzed polyacrylamide.
[0009] Polyacrylamide itself is non-corrosive and non-toxic, and is considered non-degradable as its monomer AM. It is used in small quantities and is itself a soil conditioner that can increase the soil's aggregate structure. The amide groups contained in the molecule slowly hydrolyze in the soil, which can increase the soil's nitrogen content, thus greatly reducing pollution to farmland and the environment.
[0010] Preferably, the bentonite is sodium bentonite.
[0011] Preferably, the crosslinking agent is aluminum sulfate and sodium sulfate, and the mass ratio of aluminum sulfate to sodium sulfate is (1-2):1.
[0012] Preferably, the loss-reducing agent is potassium polyacrylate.
[0013] Preferably, the emulsifier is SE-10.
[0014] Soda ash, as a dispersant, can improve the activity of mud. At the same time, according to the principle of mud treatment based on the double electric layer theory, after adding sodium-containing treatment agents such as soda ash to the matrix, sodium ions will replace the original calcium ions in the clay, thereby converting calcium clay into sodium clay, thus improving the dispersion of mud.
[0015] Preferably, the green and environmentally friendly cross-linked shield tunneling mud system further includes 0.01-0.05 parts of hydrogel-type antifreeze, wherein the hydrogel-type antifreeze comprises the following raw materials in parts by weight: 6-8 parts of carboxylated chitosan, 1-3 parts of hydroxyl-containing cellulose, 0.3-0.7 parts of magnesium chloride solution, 1-3 parts of acrylamide, 0.1-0.3 parts of N,N-methylenebisacrylamide solution and 0.1-0.3 parts of 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone.
[0016] When carboxylated chitosan, hydroxyl-containing cellulose, and acrylate are used together, they form a three-network composite hydrogel system. This system has excellent adhesion, self-healing properties, and strain buffering properties. It can effectively adhere to the components of the green and environmentally friendly cross-linked shield tunneling mud system, while also providing a certain strain buffering when the temperature changes, thus achieving excellent antifreeze performance.
[0017] In addition, the addition of magnesium chloride solution can promote the formation of metal ion cross-linking bonds in the hydrogel-type antifreeze system, thereby eliminating the need for a complicated soaking process and making the preparation of hydrogel-type antifreeze more convenient and faster.
[0018] Preferably, the hydroxyl-containing fiber is a PIPD fiber.
[0019] PIDI fiber is a high-strength, high-modulus, flame-retardant, heat-resistant, compression-resistant, and UV-resistant organic fiber. It also has excellent adhesive properties. At the same time, there are a large number of -OH and -NH on the molecular chain of PIDI fiber, which form a three-dimensional hydrogen bond network structure between and within molecules, further improving the antifreeze performance of the green and environmentally friendly cross-linked shield tunneling mud system.
[0020] Preferably, the preparation method of the hydrogel-type antifreeze is as follows: carboxylated chitosan, PIPD fiber, magnesium chloride solution, acrylamide, N,N-methylenebisacrylamide solution and 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone are mixed, stirred in an ice-water bath, ultrasonically degassed and injected into a mold, and irradiated with ultraviolet light for 10-15 minutes to obtain the hydrogel-type antifreeze.
[0021] Secondly, this application provides a method for preparing a green and environmentally friendly cross-linked shield tunneling mud system, using the following technical solution:
[0022] A method for preparing a green and environmentally friendly cross-linked shield tunneling mud system includes the following steps:
[0023] S1. Weigh 80 parts of water, then add 2 parts of bentonite to the water, and stir thoroughly at 4500 r / min until uniform, and let stand for 20 hours.
[0024] S2. Weigh 10 parts of water, then add 0.075 parts of thickening and slag-forming agent to the water, and then stir thoroughly at a speed of 200 r / min and let stand for 4 hours.
[0025] S3. Weigh 10 parts of water, then add 0.04 parts of crosslinking agent to the water, and then stir thoroughly at a speed of 200 r / min and let stand for 10 min.
[0026] S4. Mix the solutions from S1, S2, and S3 with 0.09 parts of soda ash, 0.07 parts of loss reducer, and 0.05 parts of emulsifier at a speed of 1000 r / min, and then let stand for 10 min to obtain a green and environmentally friendly cross-linked shield tunneling mud system.
[0027] In summary, this application has the following beneficial effects:
[0028] 1. Polyacrylamide itself is non-corrosive and non-toxic, and is considered non-degradable as its monomer AM. It is used in small quantities and is itself a soil conditioner that can increase the soil's aggregate structure. The amide groups contained in the molecule slowly hydrolyze in the soil, which can increase the soil's nitrogen content, thus greatly reducing pollution to farmland and the environment.
[0029] 2. Soda ash, as a dispersant, can improve the activity of mud. At the same time, according to the principle of mud treatment based on the double electric layer theory, after adding sodium-containing treatment agents such as soda ash to the matrix, sodium ions will replace the original calcium ions in the clay, thereby converting calcium clay into sodium clay, thus improving the dispersion of mud.
[0030] 3. Compared with traditional bentonite slurry, the green and environmentally friendly cross-linked shield tunneling slurry system of this application has many advantages such as suitable viscosity, fast film formation rate, high film formation quality, and green environmental protection. At the same time, it reduces the amount of bentonite used by about 50-75%, while increasing the film formation efficiency of the slurry by about 40% and the water retention capacity of the slurry film by about 25%.
[0031] 4. When carboxylated chitosan, hydroxyl-containing cellulose and acrylate are used together, they will form a three-network composite hydrogel system. This system has excellent adhesion, self-healing and strain buffering properties. Thus, while effectively adhering to the components of the green and environmentally friendly cross-linked shield tunneling mud system, it can also provide a certain strain buffering when the temperature changes, thereby obtaining excellent antifreeze performance.
[0032] 5. PIDI fiber is a high-strength, high-modulus, flame-retardant, heat-resistant, compression-resistant, and UV-resistant organic fiber. It also has excellent adhesive properties. At the same time, there are a large number of -OH and -NH on the molecular chain of PIDI fiber, which form a three-dimensional hydrogen bond network structure between and within molecules, thereby effectively improving the antifreeze performance of the green and environmentally friendly cross-linked shield tunneling mud system. Attached Figure Description
[0033] Figure 1 These are the permeation time-permeation distance diagrams for Example 1, Comparative Example 1, and Comparative Examples 3-4. Detailed Implementation
[0034] The following is in conjunction with Examples 1-6, Comparative Examples 1-4, and Figure 1 This application will be described in further detail.
[0035] raw material
[0036] Hydrolyzed polyacrylamide CAS: 9003-05-8; Sodium bentonite CAS: 85049-30-5; Aluminum sulfate CAS: 10043-01-3; Sodium sulfate CAS: 7757-82-6; Potassium polyacrylate CAS:
[0037] 25608-12-2; Emulsifier SE-10; Soda ash CAS: 497-19-8; Loss reduction agent Sichuan Maitwei;
[0038] Carboxylated chitosan CAS: 9012-76-4; Magnesium chloride CAS: 7786-30-3; Acrylamide CAS:
[0039] 79-06-1; N,N-Methylenebisacrylamide CAS: 110-26-9; 2-Hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone CAS: 106797-53-9; Carboxymethyl cellulose CAS:
[0040] 9000-11-7.
[0041] Example
[0042] Example 1
[0043] A green and environmentally friendly cross-linked shield tunneling mud system includes the following raw materials by weight: 100 kg water, 1 kg sodium bentonite, 0.05 kg thickening agent-hydrolyzed polyacrylamide, 0.037 parts cross-linking agent, 0.09 kg soda ash, 0.07 parts loss reducer and 0.05 parts emulsifier SE-10;
[0044] The crosslinking agents are aluminum sulfate and sodium sulfate, wherein 0.020 kg of aluminum sulfate and 0.017 kg of sodium sulfate are used.
[0045] The preparation method of the green and environmentally friendly cross-linked shield tunneling mud system includes the following steps:
[0046] S1. Weigh 80kg of water, then add 1kg of bentonite to the water, and stir thoroughly at 4500r / min until uniform, and let stand for 20h.
[0047] S2. Weigh 10kg of water, then add 0.05kg of thickening and slag-forming agent - hydrolyzed polyacrylamide to the water, and then stir thoroughly at a speed of 200r / min and let stand for 4h.
[0048] S3. Weigh 5 kg of water, then add 0.02 kg of aluminum sulfate to the water, and stir thoroughly at 200 r / min. Let stand for 4 min.
[0049] S4. Weigh 5 kg of water, then add 0.017 kg of sodium sulfate to the water, and then stir thoroughly at a speed of 200 r / min and let stand for 4 min.
[0050] S5. Mix the solutions from S1, S2, S3, and S4 with 0.09 kg of soda ash, 0.07 kg of loss reducer, and 0.05 kg of emulsifier SE-10 at a speed of 1000 r / min, and then let stand for 10 min to obtain a green and environmentally friendly cross-linked shield tunneling mud system.
[0051] Example 2
[0052] A green and environmentally friendly cross-linked shield tunneling mud system includes the following raw materials by weight: 100 kg water, 2 kg sodium bentonite, 0.075 kg thickening agent-hydrolyzed polyacrylamide, 0.043 parts cross-linking agent, 0.09 kg soda ash, 0.07 parts loss reducer and 0.05 parts emulsifier SE-10;
[0053] The crosslinking agents are aluminum sulfate and sodium sulfate, wherein 0.023 kg of aluminum sulfate and 0.02 kg of sodium sulfate are used.
[0054] The preparation method of the green and environmentally friendly cross-linked shield tunneling mud system includes the following steps:
[0055] S1. Weigh 80kg of water, then add 2kg of bentonite to the water, and stir thoroughly at 4500r / min until uniform, then let stand for 20h.
[0056] S2. Weigh 10kg of water, then add 0.075kg of thickening and slag-reducing agent - hydrolyzed polyacrylamide to the water, and then stir thoroughly at a speed of 200r / min and let stand for 4h.
[0057] S3. Weigh 5 kg of water, then add 0.02 kg of aluminum sulfate to the water, and stir thoroughly at 200 r / min. Let stand for 4 min.
[0058] S4. Weigh 5 kg of water, then add 0.017 kg of sodium sulfate to the water, and then stir thoroughly at a speed of 200 r / min and let stand for 4 min.
[0059] S5. Mix the solutions from S1, S2, S3, and S4 with 0.09 kg of soda ash, 0.07 kg of loss reducer, and 0.05 kg of emulsifier SE-10 at a speed of 1000 r / min, and then let stand for 10 min to obtain a green and environmentally friendly cross-linked shield tunneling mud system.
[0060] Example 3
[0061] The difference from Example 2 is that 0.04 kg of hydrogel-type antifreeze is added in S5;
[0062] The hydrogel-type antifreeze agent comprises the following raw materials by weight: 7 kg carboxylated chitosan, 2 kg carboxymethyl cellulose, 0.5 kg 10 wt% magnesium chloride aqueous solution, 2 kg acrylate, 0.2 kg 20 wt% N,N-methylenebisacrylamide aqueous solution, and 0.2 kg 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone;
[0063] The preparation method of the hydrogel-type antifreeze is as follows: carboxylated chitosan, carboxymethyl cellulose, magnesium chloride solution, acrylamide, N,N-methylenebisacrylamide aqueous solution and 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone are mixed, stirred in an ice-water bath, then ultrasonically degassed and injected into a mold, and irradiated with ultraviolet light for 13 minutes to obtain the hydrogel-type antifreeze.
[0064] Example 4
[0065] The difference from Example 3 is that carboxymethyl cellulose was replaced with the same amount of PIDI fiber.
[0066] Examples 5-6
[0067] The difference from Example 4 is that the amount of each component added in the hydrogel-type antifreeze is different, as shown in Table 1.
[0068] Table 1. Dosage of each component added to the hydrogel-type antifreeze in Examples 4-6 (kg)
[0069]
[0070] Comparative Example
[0071] Comparative Example 1
[0072] A cross-linked shield tunneling slurry, which is prepared by mixing 2 kg of water with 0.12 kg of sodium bentonite.
[0073] Comparative Example 2
[0074] A cross-linked shield tunneling slurry is prepared by mixing 2 kg of water, 0.12 kg of sodium bentonite and 0.0018 kg of carboxymethyl cellulose.
[0075] Comparative Example 3
[0076] A commercially available pulping agent I, model number Lanjin 1.
[0077] Comparative Example 4
[0078] A commercially available pulping agent II, model number Lanjin 2.
[0079] Performance testing
[0080] Detection methods
[0081] I. Basic Performance Testing of Mud
[0082] Three samples were taken from Examples 1-2 and Comparative Examples 1-2 respectively. The API filtration rate, funnel viscosity, dynamic shear force and gel strength of the above samples were then tested using a Soo-Schwarz funnel viscometer (Type 1006 mud viscometer), a six-speed rotational viscometer (HTD-06) and an API filtration loss meter (ZNS-2A). The average values were taken and the test data are shown in Table 2.
[0083] Table 2 Basic Performance Test Table of Examples 1-2 and Comparative Examples 1-2
[0084]
[0085] II. Water Retention Performance Test of Mud Permeation Film Formation
[0086] Three samples were taken from Example 1, Comparative Example 1, and Blue Brocade Type 1 and Blue Brocade Type 2, respectively. The samples were then tested using a simulated formation permeability column test device (made of plexiglass column with a diameter of 20cm and a height of 42cm) and an automatic water collection system (JJ5000 electronic balance), and the average value was taken.
[0087] The comparative experiments all used a permeability coefficient of 2.04 × 10⁻⁶. -2 For a sandy saturated formation with a density of cm / s, after the formation and the upper mud were added, the instrument was sealed and a pressure of 100 kPa was applied to the mud. The drain valve at the bottom of the device was opened to allow the upper mud to permeate into the formation under stable pressure. The changes in the outflow of water from the lower valve and the changes in pore water pressure at different depths of the formation were observed and recorded during the mud permeation process. The test data are shown in Table 3.
[0088] Table 3. Water retention performance test results for Example 1, Comparative Example 1, and Comparative Examples 3-4.
[0089] Example 1 642 26 1.5 Comparative Example 1 1003 25 3 Comparative Example 3 - Blue Brocade Type 1 1086 39.4 3.5 Comparative Example 4 - Blue Brocade Type 2 1632 31.5 7.5
[0090] III. Mud Toxicity Test
[0091] Three samples were taken from Examples 1-2, and their toxicity was tested using a microplate multi-function analyzer (GloMax-Multi2011ZSIR0369US). The test method was as follows: the sample was mixed with a 3% NaCl aqueous solution at a volume ratio of 1:9, allowed to stand for 60 minutes, and the middle suspension was taken as the test solution. This solution was diluted to different concentrations, and standard bacterial strains were used to determine the luminescence of the test solution relative to the 3% NaCl aqueous solution. When the relative luminescence of the luminescent bacteria decreased by half, the concentration of the test solution was recorded as the LC50 of the shield slurry. 50 .
[0092] The results of the toxicity tests on the mud according to the toxicity standards and Examples 1-2 are shown in Table 4:
[0093] Table 4 Toxicity Standards and Mud Toxicity Testing Tables for Examples 1-2
[0094]
[0095] IV. Antifreeze performance test
[0096] Six samples were taken from Examples 2-6 respectively. Then, the flexural strength of three of the samples was tested according to GB / T 17669-1999 "Test Method for Flexural Strength of Building Mortar" and the average value was recorded as the original flexural strength.
[0097] For the other three samples, the samples were cured for the first 24 days. After 24 days, they were taken out and soaked in water at 20°C for 4 days. Then, they were subjected to freeze-thaw treatment. The freeze-thaw treatment was controlled with a minimum temperature of -18°C and a maximum temperature of 5°C. The freeze-thaw cycle time was 6 hours and lasted for 2 days. After that, the flexural strength of the above three samples was tested according to GB / T 17669-1999 "Test Method for Flexural Strength of Building Mortar" and the average value was taken and recorded as the freeze-thaw treatment flexural strength.
[0098] Finally, calculate the frost resistance rate: frost resistance rate = frost-treated flexural strength / original flexural strength × 100%.
[0099] The test results are shown in Table 5.
[0100] Table 5. Antifreeze performance of Examples 1 and 3-6
[0101] Example 1 84.6% Example 5 92.1% Example 3 90.3% Example 6 92.6% Example 4 93.7%
[0102] Referring to Examples 1-2 and Comparative Examples 1-2 and in conjunction with Table 2, it can be seen that, compared with Comparative Examples 1-2, Examples 1-2 have lower API filtration loss, greater dynamic shear force, and higher gel strength. This indicates that Examples 1-2 have better slag carrying capacity, greater structural strength in a static state, stronger ability to suspend slag and soil debris particles, and at the same time reduce the amount of bentonite used by about 50-75%.
[0103] Referring to Example 1, Comparative Example 1, and Comparative Examples 3-4, and in conjunction with Table 3, Figure 1 It can be seen that, compared with Comparative Example 1 and Comparative Examples 3-4, Example 1 has a faster permeation film formation rate, shorter permeation distance, higher film quality, and better water retention performance in the early stage of mud permeation.
[0104] Referring to Examples 1-2 and in conjunction with Table 4, it can be seen that Examples 1-2 clearly meet the emission limit standards, thus demonstrating that Examples 1-2 have good environmental performance.
[0105] The reason for this is that polyacrylamide itself is non-corrosive and non-toxic, and is considered non-degradable as its monomer AM. It is used in small quantities, and polyacrylamide itself is a soil conditioner that can increase the soil's aggregate structure. The amide groups contained in the molecule slowly hydrolyze in the soil, which can increase the soil's nitrogen content, thus greatly reducing pollution to farmland and the environment.
[0106] Soda ash, as a dispersant, can improve the activity of mud. At the same time, according to the principle of mud treatment based on the double electric layer theory, after adding sodium-containing treatment agents such as soda ash to the matrix, sodium ions will replace the original calcium ions in the clay, thereby converting calcium clay into sodium clay, thus improving the dispersion of mud.
[0107] Referring to Examples 1 and 3 and in conjunction with Table 5, it can be seen that the antifreeze rate of Example 3 is significantly improved compared to Example 1. This indicates that the addition of hydrogel-type antifreeze can effectively improve the antifreeze performance of the green and environmentally friendly cross-linked shield tunneling mud system.
[0108] The reason for this is that when carboxylated chitosan, hydroxyl-containing fibers, and acrylic acid are used together, they form a three-network composite hydrogel system. This system has excellent adhesion, self-healing properties, and strain buffering properties. Thus, while effectively adhering to the components of the green and environmentally friendly cross-linked shield tunneling mud system, it can also provide a certain strain buffering when the temperature changes, thereby obtaining excellent antifreeze performance.
[0109] Referring to Examples 3-4 and Table 5, it can be seen that Example 4 shows further improved antifreeze performance compared to Example 3. This indicates that, compared to carboxymethyl cellulose, the addition of PIDI fiber results in a green and environmentally friendly cross-linked shield tunneling mud system with superior antifreeze performance.
[0110] The reason for this is that PIDI fiber is a high-strength, high-modulus, flame-retardant, heat-resistant, compression-resistant, and UV-resistant organic fiber. It also has excellent adhesive properties. At the same time, there are a large number of -OH and -NH on the molecular chain of PIDI fiber, which form a three-dimensional hydrogen bond network structure between and within molecules, thereby effectively improving the antifreeze performance of the green and environmentally friendly cross-linked shield tunneling mud system.
[0111] Referring to Examples 4-6 and Table 5, it can be seen that the antifreeze rate of Examples 5-6 is slightly lower than that of Example 4. This indicates that when the amount of each component of the hydrogel-type antifreeze agent is added according to the ratio of Example 4, the prepared green and environmentally friendly cross-linked shield tunneling mud system has better antifreeze performance.
[0112] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A green and environmentally friendly cross-linked shield tunneling mud system, characterized in that, The raw materials include the following parts by weight: 90-110 parts water, 0.03-0.15 parts thickening and slag-forming agent, 1-3 parts bentonite, 0.01-0.18 parts soda ash, 0.02-0.06 parts crosslinking agent, 0.01-0.15 parts loss-reducing agent, and 0.01-0.10 parts emulsifier, wherein the thickening and slag-forming agent is hydrolyzed polyacrylamide; The crosslinking agent is aluminum sulfate and sodium sulfate, and the mass ratio of aluminum sulfate to sodium sulfate is (1-2):1; The green and environmentally friendly cross-linked shield tunneling mud system also includes 0.01-0.05 parts of hydrogel-type antifreeze, which includes the following raw materials in parts by weight: 6-8 parts of carboxylated chitosan, 1-3 parts of hydroxyl-containing cellulose, 0.3-0.7 parts of magnesium chloride solution, 1-3 parts of acrylamide, 0.1-0.3 parts of N,N-methylenebisacrylamide solution, and 0.1-0.3 parts of 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone.
2. The green and environmentally friendly cross-linked shield tunneling mud system according to claim 1, characterized in that: The bentonite is sodium bentonite.
3. The green and environmentally friendly cross-linked shield tunneling mud system according to claim 1, characterized in that: The loss-reducing agent is potassium polyacrylate.
4. The green and environmentally friendly cross-linked shield tunneling mud system according to claim 1, characterized in that: The emulsifier is SE-10.
5. The green and environmentally friendly cross-linked shield tunneling mud system according to claim 1, characterized in that: The hydroxyl-containing fiber is a PIPD fiber.
6. The green and environmentally friendly cross-linked shield tunneling mud system according to claim 5, characterized in that: The preparation method of the hydrogel-type antifreeze is as follows: carboxylated chitosan, PIPD fiber, magnesium chloride solution, acrylamide, N,N-methylenebisacrylamide solution and 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone are mixed, stirred in an ice-water bath, then ultrasonically degassed and injected into a mold, and irradiated with ultraviolet light for 10-15 minutes to obtain the hydrogel-type antifreeze.
7. A method for preparing the green and environmentally friendly cross-linked shield tunneling mud system according to any one of claims 1-6, characterized in that, Includes the following steps: S1. Weigh 80 parts of water, then add 2 parts of bentonite to the water, and stir thoroughly at 4500 r / min until uniform, and let stand for 20 hours. S2. Weigh 10 parts of water, then add 0.075 parts of thickening and slag-forming agent to the water, and then stir thoroughly at a speed of 200 r / min and let stand for 4 hours. S3. Weigh 10 parts of water, then add 0.04 parts of crosslinking agent to the water, and then stir thoroughly at a speed of 200 r / min and let stand for 10 min. S4. Mix the solutions from S1, S2, and S3 with 0.09 parts of soda ash, 0.07 parts of loss reducer, and 0.05 parts of emulsifier at a speed of 1000 r / min, and then let stand for 10 min to obtain a green and environmentally friendly cross-linked shield tunneling mud system.
Citation Information
Patent Citations
Cross-linking type low solid mud for breast wall in rock-soil drilling project or groove drilling and digging project and preparing method thereof
CN102676138A